Scorched earth - Muchamore, Robert (London : Hodder Children's Books, 2013)
In the summer of 1944 with the war turning against the Nazis the Henderson's boys embark on their final and most dangerous mission.
Young Adult
Young Adult
Keywords: Intelligence service -- Fiction; World War, 1939-1945 -- Secret service -- Fiction; Historical fiction; Intelligence service -- Fiction; Spy stories; World War, 1939-1945 -- Secret service -- Fiction; Historical fiction; Spy stories